Konsep Asy’ariyah dan Relevansinya Dalam Kehidupan - Prischa, Farra Sintiya; Daniyarti, Wiwi Dwi (Pascasarjana IAIN Metro, 2023)
Human life will forever be well maintained, if humans use and develop their nature in life. Human nature does not exist without a reason, human nature exists because it is a provision for humans to live on earth as caliphs. Human nature has supports, namely reason, heart and actions. Reason provides guidance in actions guided by the revelation or words of Allah SWT, while the heart harmonizes actions because there are instructions for goodness captured by the cleanliness of the human heart. Mind and heart that are in harmony with the goodness and guidance of Allah SWT will create good actions as a form of human power given by Allah SWT. Human kasb is the power given by Allah SWT to the human body or physique to make it happen. Humans who understand this will carry out appropriate efforts from the guidance of revelation that captures reason and carry out actions without hypocrisy because they are in line with what is in their hearts. This study uses a qualitative approach with a library method by collecting the necessary data sources related to the discussion. The concept of fitrah with its discussion of the mind, heart and actions or human will in the Ash'ariyah view will be relevant to life so that it can continue to be discussed and developed. This study tries to explore the concept of reason, heart and actions from Ash'ariyah thought. Previously there was a study that discussed in detail regarding kasb, so this study discusses it in its entirety, namely reason, heart and actions or kasb